From the to project to the action: history of creation and labor of UNIFÉ' S Family Institute - Vidal Cabeza de Tarazona, Gisela (2014)
This article develops the history of the creation of the Family Institute of UNIFE, as well as the activities and actions taken in defense oflife, the individual, the family and women from its inception until today ..